Cults, Congregations, and conversi The Cistercians of Coupar Angus and their Chapels - Hodgson, Victoria (2018)
Chapels were commonly found in Cistercian ownership throughout Europe but remain an understudied topic, particularly in medieval Scotland. Yet their study has the potential to make a significant contribution to our understanding of the ways in which Cistercian houses interacted with local culture and lay populations through the cult of saints. This article examines those chapels which pertained to the abbey of Coupar Angus, considering the forms of worship which took place within them. It offers an interpretation of 'chapels on grange lands' as not necessarily synonymous with 'grange chapels' as they have typically been understood, while giving equal attention to chapels under Coupar's control elsewhere. In doing so, insight is gained into the evolving religious landscape of medieval Scotland and the role played by this abbey within it.